Midlatitude Oceanic Fronts Strengthen the Hydrological Cycle Between Cyclones and Anticyclones - S. Okajima; H. Nakamura; T. Spengler (Geophysical Research Letters)
Abstract The Kuroshio‐Oyashio Extension and Gulf Stream oceanic frontal zones are characterized by enhanced activity of synoptic‐scale cyclones and anticyclones and vigorous air‐sea heat and moisture exchange in the cold season. However, the time‐mean air‐sea exchange attributed separately to cyclones and anticyclones has not been assessed. Here we quantify cyclonic and anticyclonic contributions around the frontal zones to surface turbulent heat fluxes, precipitation, and the associated hydrological cycle using atmospheric general circulation model experiments with observed and artificially smoothed sea‐surface temperature gradients. The evaluation reveals that precipitation exceeds evaporation climatologically within cyclonic domains while evaporation dominates within anticyclonic domains. These features as well as the net moisture transport from anticyclonic to cyclonic domains are all enhanced by the sharpness of the frontal zones. Oceanic frontal zones thus climatologically act to strengthen the hydrological cycle. These findings aid our understanding of the relationship between midlatitude air‐sea interactions on synoptic‐ and longer‐time scales.